An Audit of Rigid Bronchoscopy - Mahboob Yazdani Khan, Mahboob Yazdani Khan (Journal of Rawalpindi Medical College, 2018)
Background: To determine the utility of rigid bronchoscopy in terms of age, sex and seasonal variations. Methods: In this descriptive study all patients undergoing rigid bronchoscopy were included. The data was analyzed on the basis of age, sex, indication, nature of foreign body and seasonal variations. The patients were divided as per indication of bronchoscopy in individual cases. As regard nature of foreign body, patients were divided into those having metallic and non-metallic foreign bodies. Special stress was paid to evaluate incidence of rigid bronchoscopies in relation 2 main seasons of this part of the world i.e winter and summer. The outcome of seasonal variations in incidence and results of bronchoscopies was analyzed. Results: Age ranged from 1 year to 60 years. The male to female ratio was equivalent as 10 patients in each group. There were 12 children and 8 adults. The most common indication of bronchoscopy was foreign body(65%). . Out of 13 cases of bronchoscopy for foreign body bronchus 84.6% were children. There were 11 cases of bronchoscopy (55%) in winter season and 45% in summer. Peanut (90.9%) was the commonest foreign body encountered in paediatric age group. There were no complications of bronchoscopy except 2 cases with failure to remove foreign body in first sitting but successfully removed in second sitting. Conclusion: Foreign body bronchus is the most common indication of rigid endoscopy and majority of the patients are children under the age of 12. The most common foreign body bronchus is peanut especially in winter season.